MOTIVASI USAHA PERTANIAN PERKOTAAN DI PEKANBARU - Dian Chintya Dewi; Hajry Arief Wahyudy (UIR Press, 2022)
The purpose of this study is to find out what is the biggest motivation of farmers to develop urban farming in Pekanbaru. This study used a survey method. Based on the information of the key respondent, in this case the director of Komunitas Hidroponik Riau, 17 respondents were obtained using the snowball sampling technique. The level of motivation is measured on a Likert scale, and then the highest average score for each indicator is calculated. Based on the research results, it is known that, in general, the motivation level of Pekanbaru farmers in the development of urban agriculture is classified as very good with an average of .53. Financial motivation is the highest, with an average of .76 (very good). These results indicate that economic factors are the strongest motivating factor for the development of urban farming in Pekanbaru.